Permataku Monitoring System and Student Development of Taska Qaseh Ummi: Sistem Pemantauan Permataku dan Perkembangan Pelajar Taska Qaseh Ummi - Mohd Salleh, Nurul Ain; Hassan, Norlida (Applied Information Technology And Computer Science, 2022)
The Permataku Taska Qaseh Ummi Monitoring System is a web -based system aimed at facilitating the management of Taska Qaseh Ummi to be more efficient and systematic. The objective of the development of this system is to assist the daily management of the nursery by using a computerized system, to replace manual work procedures using paper. These tasks involve the process of staff having to fill out student diaries daily and often also occurs the loss of student diaries. This conventional method does not record student progress as a reference for parents and nursery managers. Therefore, the development of Permataku Taska Qaseh Ummi Monitoring System is expected to help managers, staff and parents achieve this system and directly this system allows staff to record all daily activities of students and fill in student progress online and not using daily logbooks. The system is developed based on a prototype methodology that has six phases. The system is also developed using Sublime Text software as the coding medium and Xampp as the database and system server. In conclusion, the Permataku Taska Qaseh Ummi Monitoring System is expected to facilitate the management of data and information for the management of the nursery, managers, staff, and parents of children.